Empowering bawor durian farmers through training in bush pepper cultivation using stem cuttings - Suyadi, Aman; Rusman, Ade; Wicaksono, Galih; Syandana, Wigar Zada (Universitas Muhammadiyah Magelang, 2025)
The decline in sales of Bawor durian seedlings, caused by the widespread proliferation of similar cultivars across Indonesia, has become a significant challenge for the Ngudi Makmur and Gangga Mulya Farmer Groups. This training program was designed as an innovative solution to provide farmers with an alternative income source through intercropping with bush pepper (Piper nigrum) cultivation. The main challenge identified was the farmers' lack of technical knowledge and skills in propagating this type of pepper. Therefore, this program aimed to enhance their capacity in bush pepper propagation techniques using stem cuttings. The capacity-building was conducted through various methods, including continuous mentoring, lectures, focused group discussions, and hands-on training. The lecture and discussion sessions covered the basic theory of propagation, such as identifying ideal cutting materials, growth media, and environmental factors influencing success. The practical sessions focused on the techniques of cutting stems and transplanting seedlings into the growth media. The results of this program showed a significant increase in the participants' knowledge and skills. A propagation demoplot was also successfully established. This initiative not only aims to boost farmers' income but also supports more sustainable agricultural practices.